1998
DOI: 10.1046/j.1365-2427.1998.00331.x
|View full text |Cite
|
Sign up to set email alerts
|

Does sediment resuspension have persistent effects on phytoplankton? Experimental studies in three shallow lakes

Abstract: 1. The persistence of effects of sediment resuspension on chlorophyll a, phytoplankton production and plant nutrients was examined by artificially resuspending sediment in enclosures in three shallow lakes and monitoring concentrations for 4–8 days. Realism was assessed by relating initial suspended solids concentrations to those observed during natural wind events. 2. Positive effects on the phytoplankton, persisting for at least 4–6 days were detected in eight of the nine experiments, and similar effects on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
72
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(75 citation statements)
references
References 32 publications
1
72
0
Order By: Relevance
“…If the increased nutrient supply released the other phytoplankton species from nutrient limitation, and if these were able to utilise nitrogen faster than C. closterium, this would explain why the growth of C. closterium slowed down. Our results are supported by the results of an experimental study on the effects of sediment resuspension on phytoplankton that showed that the associated relief of nitrogen deficiency stimulated biomass and algal productivity in shallow coastal systems (Ogilvie and Mitchell, 1998), and by the results of a monitoring study on a brackish system, where the biovolume of some phytoplankton groups (cryptophyceae, diatoms, dinoflagellates) was positively correlated with turbidity (Zehrer et al, 2015).…”
Section: Effects Of Turbiditysupporting
confidence: 82%
See 2 more Smart Citations
“…If the increased nutrient supply released the other phytoplankton species from nutrient limitation, and if these were able to utilise nitrogen faster than C. closterium, this would explain why the growth of C. closterium slowed down. Our results are supported by the results of an experimental study on the effects of sediment resuspension on phytoplankton that showed that the associated relief of nitrogen deficiency stimulated biomass and algal productivity in shallow coastal systems (Ogilvie and Mitchell, 1998), and by the results of a monitoring study on a brackish system, where the biovolume of some phytoplankton groups (cryptophyceae, diatoms, dinoflagellates) was positively correlated with turbidity (Zehrer et al, 2015).…”
Section: Effects Of Turbiditysupporting
confidence: 82%
“…Due to the mitigating effect of turbidity, resistance was slightly higher than in the 26°C heat wave only treatment. Similar to the turbid 22°C heat wave, sediment addition released several species from nitrogen limitation (Hamilton and Mitchell, 1997;Hansen et al, 1997;Ogilvie and Mitchell, 1998). C. closterium was lost during the turbid 26°C heat wave.…”
Section: Resistance and Resilience To The Cumulative Effects Of Heat mentioning
confidence: 97%
See 1 more Smart Citation
“…Another more sustained response may take place as inputs of inorganic and organic particulate and dissolved nutrients from land or sediment enhance biological production, both primary (e.g. Mura et al 1996, Ogilvie & Mitchell 1998) and bacterial (e.g. Wainright 1987, Gré-mare et al 2003, Alonso-Sáez et al 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Søndergaard et al [8] concluded that phosphorus release from sediments increased 20-30-fold during resuspension events in a shallow Danish lake. Ogilvie and Mitchell [14] modified the release rates of regenerated dissolved nutrients from the sediments resuspension. Qin et al [15] analyzed the influence on sediments suspension by wave and current of Taihu Lake, considered that the sediments suspended extensively when wind velocity was above 6.5 m/s.…”
Section: Introductionmentioning
confidence: 99%